Impact of COVID-19 on the Dental Community - Howaldt, Hans-Peter; Attia, Sameh (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The COVID-19 pandemic is considered to be a global public health emergency. Due to its route of transmission via contact with droplets and aerosols, dentists are at high risk of acquiring an infection while treating patients. The impact of the coronavirus on the dental community is eminent, and the greatest challenge is how we can offer dental treatment despite the outbreak. Dental education programs in both under- and postgraduate forms will also suffer from the ramifications of the pandemic. This topical collection offers many perspectives on the management of the COVID-19 crisis within the dental community.